The use of between-leg asymmetries in jump performance as a screening tool in female team sport athletes - Lockie, R. G.; Schultz, A. B.; Luczo, T. M.; Berry, S. P.; Jeffriess, M. D.; Callaghan, S. J.; Jordan, C. A. (Journal of Athletic Enhancement, 2013)
Study background: The Functional Movement Screen (FMS, deep squat [DS], hurdle step, in-line lunge [ILL], shoulder mobility, active straight-leg raise, trunk stability push-up [TSPU], rotary stability) assesses individual movement capabilities. Unilateral jumps, and between-leg asymmetries, are also used for screening. Relationships between an established screening protocol (FMS) and unilateral jump asymmetries have not been investigated.